Value-Oriented English Learning Materials: A Conceptual Review of Textbooks, Local Content, and Character Education - Ghifari, Akhmad; Norfansyah, Reihan; Hakim, Muhammad; Widiastuty, Hesty (Universitas Muhammadiyah Barru, 2026)
This study explores the role of value-oriented English textbooks in connecting language learning with moral, cultural, and character education values. In many Indonesian classrooms, commercial textbooks dominate and often fail to represent local contexts or ethical perspectives. Using a qualitative library research design grounded in a constructivist approach, this study reviews 25 relevant publications published between 2020 and 2025. The data were examined through coding and thematic interpretation to identify major ideas in the development of value-based English materials. The findings reveal that textbooks designed with cultural and moral awareness can strengthen students’ communication skills, ethical sensitivity, and sense of identity. However, most current textbooks still prioritize standardized global content over local and spiritual values. Therefore, the study emphasizes the need for English textbooks that balance linguistic goals with character formation, particularly within Islamic and Indonesian educational contexts.